Salivary Alkaline Phosphatase as a Non-Invasive Biomarker in Early Detection of Oral Submucous Fibrosis - Inam Ur Rehman, Muhammad Ahmed Saleem, Bhunesha Devi, Ikram Ullah,Anees Ur Rehman, Muhammad Azeem Khan (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Oral submucous fibrosis (OSF) is a chronic precancerous condition marked by progressive fibrosis of the oral mucosa and restricted mouth opening. Early detection